The prince problem - Vande Velde, Vivian (Scholastic Press, 2018)
Prince Telmund has been cursed to transform into a new animal every time he falls asleep and Princess Amelia has been kidnapped by the dangerous Prince Sheridan; if either of them want a happy ending they will have to work together.